Factors Influencing Anemi In Pregnant Women At Trimurti Clinic - Rambe, Resti Fauziah; Simarmata, Mesrida (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Introduction : Anemia is a condition in which the mother's hemoglobin level is less than 11g/dl due to a lack of iron in red blood cells. The criteria for anemia can be divided into 3, namely mild, moderate and severe anemia . The impact of this anemia can be on the mother and baby. Objective : To analyze the factors that influence the occurrence of anemia in pregnant women at the Trimurti Clinic. Method: observational analytic with approach cross sectional study . Population and Sample: all pregnant women in the third trimester at the Trimurti Badar Setia Clinic, Percut Sei Tuan District, Deli Serdang Regency, as many as 35 people with a total population sampling technique, the number of samples was 35 people. Place and time: Trimurti Badar Setia Clinic, Percut Sei Tuan District , Deli Serdang Regency, North Sumatra Province, April-July 2024. Results : In terms of nutrition of pregnant women, it was found that the p value = 0.503 > 0.05, so there is no relationship between the incidence of anemia and the nutritional status of respondents. From sleep patterns, the p value = 0.025 was found and in terms of socio-economics, the p value = 0.008 <0.05 This means that there is a relationship between the incidence of anemia and the socio-economics of respondents at the Trimurti Clinic Conclusion : There is no relationship between nutritional status and the incidence of anemia and there is a relationship between dietary patterns and socio-economics with the incidence of anemia in pregnant women in the third trimester at the Trimurti Clinic.